Participatory future visions of collaborative agroecological farmer-pastoralist systems in Tanzania. Issue 4 (21st April 2023) - Johansson, Emma; Martin, Respikius; Mapunda, Kenneth M.
ABSTRACT: Agroecology is increasingly promoted as a way to create just and sustainable farm- and food systems. Although there are multiple initiatives to scale up agroecology, current socio-political structures often hinder its potential to transform food systems. This study uses participatory approaches to create paintings that envision agroecological futures in the context of increased farmer-pastoralist collaborations in Tanzania, how they would function, and what political action is needed to support such futures. The visions are based on focus group discussions with agroecological farmers and pastoralists, and a multi-stakeholder workshop with farmer and pastoralist representatives, innovative food system actors, and researchers. We find that the envisioned transformation of the food system would lead to positive effects on farmers' and pastoralists' income, autonomy, long-term planning, and producers' and consumers' health. We conclude that new policies and financial support systems are needed to enable the expansion of agroecological farming and food systems, by increasing the availability of organic markets, supporting domestic botanicals production, and by creating more inclusive and just food value chains.